Utilization of the E-Exam Application in Evaluating Student Learning Outcomes at Madrasah Aliyah Fathul Ulum Gabus, Grobogan Regency - Ahmad, Faiz; Syihabuddin, Muhammad Arif (Interdisciplinary Journal of Social Sciences, 2025)
The e-exam application is a digital system designed to facilitate the online assessment of student learning outcomes. This application allows students to take exams from different locations using internet-connected devices. Equipped with features such as question creation, time management, randomized question and answer order, and automated scoring, the platform significantly enhances the efficiency of exam administration. MA Fathul Ulum, located in Pandanharum Village, Gabus District, Grobogan Regency, utilizes the e-exam application to evaluate students’ learning outcomes particularly in Islamic Religious Education (PAI) making it easier for teachers to distribute and randomize exam questions. This study aims to explore the utilization of the e-exam application in assessing students and to understand its implications for online-based learning evaluation at MA Fathul Ulum Gabus. A qualitative approach is employed to gain an in-depth understanding of how the e-exam application functions as a learning evaluation tool. The research process is expected to produce descriptive data in the form of written or verbal information from teachers and students, which can be observed to explain the application’s use. The findings reveal that the e-exam application has been effectively implemented, from the planning stage to post-exam follow-up. Furthermore, its application has had a positive impact on both teachers and students, contributing to the improvement of exam quality at MA Fathul Ulum Gabus.